7-Hydroxymatairesinol improves body weight, fat and sugar metabolism in C57BJ/6 mice on a high-fat diet. Issue 7 (14th August 2018) - Biasiotto, Giorgio; Zanella, Isabella; Predolini, Federica; Archetti, Ivonne; Cadei, Moris; Monti, Eugenio; Luzzani, Marcello; Pacchetti, Barbara; Mozzoni, Paola; Andreoli, Roberta; De Palma, Giuseppe; Serana, Federico; et al.
Abstract: 7-Hydroxymatairesinol (7-HMR) is a plant lignan abundant in various concentrations in plant foods. The objective of this study was to test HMRLignan™, a purified form of 7-HMR, and the corresponding Picea abies extract (total extract P. abies ; TEP) as dietary supplements on a background of a high-fat diet (HFD)-induced metabolic syndrome in mice and in the 3T3-L1 adipogenesis model. Mice, 3 weeks old, were fed a HFD for 60 d. Subgroups were treated with 3 mg/kg body weight 7-HMR (HMRLignan™) or 10 mg/kg body weight TEP by oral administration. 7-HMR and TEP limited the increase in body weight (−11 and −13 %) and fat mass (−11 and −18 %) in the HFD-fed mice. Epididymal adipocytes were 19 and −12 % smaller and the liver was less steatotic (−62 and −65 %). Serum lipids decreased in TEP-treated mice (−11 % cholesterol, −23 % LDL and −15 % TAG) and sugar metabolism was ameliorated by both lignan preparations, as shown by a more than 70 % decrease in insulin secretion and insulin resistance. The expression of several metabolic genes was modulated by the HFD with an effect that was reversed by lignan. In 3T3-L1 cells, the 7-HMR metabolites enterolactone (ENL) and enterodiol (END) showed a 40 % inhibition of cell differentiation accompanied by the inhibited expression of the adipogenic genes PPARγ, C/EBPα and aP2 . Furthermore, END and ENL caused a 10 % reduction in TAG uptake in HEPA 1–6 hepatoma cells. In conclusion, 7-HMR and TEP reduce metabolic imbalances typical of the metabolic syndrome and obesity in male mice, whereas their metabolites inhibit adipogenesis and lipid uptake in vitro .